MAHKAMAH KONSTITUSI SEBAGAI POSITIVE LEGISLATURE DALAM PENGUJIAN UNDANG-UNDANG TERHADAP UNDANG-UNDANG DASAR 1945 - Syara Nurhayati; Mexsasai Indra; Junaidi ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Constitutional Court as one of the institutions in judicial power holders, get special attention because the laws were issued. Product legal form that is both positive legislature decision considered to have displacement of the authority Constitutional Court from a negative into a positive legislature. The legal conditions cause various polemics and phenomena in the system of constitutional law in Indonesia, that related validity constitution and implementation of the positive legislature’s decisions. Purpose of this study was to determine the constitutionality of positive legislature decisions in Indonesia and implementation of the decision by the government in Indonesia’s legal system. This research is a normative study, which the authors tried to collect and analyze data on the writing of literature. The source of data is divided into primary, secondary and tertiary data. Constitutionality of the positive legislture’s decisions by Constitutional Court when viewed under Article 24C of the 1945 Constitution is not contradictory. Because the Indonesian constitution does not provide authority to limit the Constitutional Court issued a legal product. In addition, the legal reasoning in the Constitutional Court issued a positive legislatur’s decision needs to be considered in valid decision of the Constitutional Court. Where most of the legal considerations given in the Court issued a positive legislature’s decision is to achieve justice for the substantive constitutional rights holders. Whereas, for the implementation of positive legislature’s decision if not immediately followed by legislator, is valid since it was decided in court. Given the Indonesian legal system that is more influenced by positivism, needs to be made to understand the written regulations related to the authority of the Constitutional Court to issue a ruling in particular legal product that is positive legislature. In addition, for the effectiveness of the delivery of law in Indonesia should also be made binding rules for the legislator in order to more quickly respond to any product preformance law issued by the Constitutonal Court therefore do not trigger a legal vacuum in Indonesia’s legal system .Keywords: positive Legislature, constitutionality, legal consequences.